An Analysis of AI Utilization in Learning Basic-Level Mandarin Writing Skills - Pamuji, Dian Yuni; Marsuki, Ria Riski; Agwinanda, Almira; Rathnayake, R.M.P.P. (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
The development of technology, particularly Artificial Intelligence (AI), has brought significant changes in various aspects of life, including education. The presence of AI has opened new opportunities to create a more effective, interactive, and adaptive learning process tailored to students’ needs. This technology can be applied in nearly all aspects of academic learning, from providing information resources to supporting cognitive processes and practice activities. In the context of language learning, especially Mandarin writing skills, AI plays an important role as a learning tool that helps students overcome various challenges, such as difficulties in understanding sentence structures, writing hanzi, and composing grammatically correct paragraphs. This study employed a mixed-methods research approach using a convergent parallel design, which combines quantitative and qualitative data to gain a comprehensive understanding. The findings indicate that AI can serve as an effective learning aid when used appropriately and responsibly. In writing skills, AI has been shown to assist students in understanding vocabulary, sentence structure, translation, and organizing short, structured paragraphs. However, the use of AI should be guided to ensure that students do not become overly dependent on it, but rather use the technology to strengthen their conceptual mastery and develop independent writing abilities. Therefore, AI should function as a supportive learning tool, not as a replacement for the teacher’s role in the Mandarin language learning process.